Beyond specimens: linking biological collections, functional ecology and biodiversity conservation - Castillo-Figueroa, Dennis (2018)
Several anthropogenic pressures are threatening biodiversity and may increase in the next years, altering ecological processes and ecosystem services. Biological collections offer a rich source of information to develop studies of functional ecology and biodiversity conservation. Key information related to morphology, physiology and life history could be obtained through functional traits provided by specimens in biological collections. Additionally, museum collections present a great potential for document changes of habitat disturbance, using response/effect framework, functional diversity measures, and fluctuating asymmetry approaches. Despite limitations of specimens in data such as abundance, imprecisions in specimen´s georeferencing, errors in taxonomic identification and the poor preservation state of some specimens, biological collections contain vast data banks, which could be useful in the contribution of key information for land use management and conservation planning.